Competence, Work Environment and Work Discipline on Employee Performance - Shofiyah, Anira Gita Nur; Yendra, Yendra; Marihi, La Ode (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to explore the simultaneous influence of competence, work environment, and work discipline on employee performance at the BKPSDM Office of Jayapura Regency. Research Design and Methodology: The research employs a quantitative approach using a survey method. Data was collected from 95 respondents, all employees at the BKPSDM Office. The data were analyzed using multiple linear regression with the aid of SPSS version 22. The study's design includes the examination of variables such as competence, work environment, and work discipline, with controls and conditions appropriate for assessing their collective impact on performance. Findings and Discussion: The findings indicate that competence, work environment, and work discipline positively and significantly affect employee performance. The study reveals that a conducive work environment and high work discipline amplify the impact of competence on performance. This underscores the importance of a holistic approach in human resource management, where these three elements synergistically create optimal working conditions. Implications: The study's implications highlight the necessity of investing in competency development, creating supportive work environments, and enforcing fair and transparent work discipline. Future research is recommended to explore the interaction between these factors and other variables.